Influence of air mass origin on aerosol properties at a remote Michigan forest site. (April 2015) - VanReken, T.M.; Mwaniki, G.R.; Wallace, H.W.; Pressley, S.N.; Erickson, M.H.; Jobson, B.T.; Lamb, B.K.
Abstract: The northern Great Lakes region of North America is a large, relatively pristine area. To date, there has only been limited study of the atmospheric aerosol in this region. During summer 2009, a detailed characterization of the atmospheric aerosol was conducted at the University of Michigan Biological Station (UMBS) as part of the Community Atmosphere–Biosphere Interactions Experiment (CABINEX). Measurements included particle size distribution, water-soluble composition, and CCN activity. Aerosol properties were strongly dependent on the origin of the air masses reaching the site. For ∼60% of the study period, air was transported from sparsely populated regions to the northwest. During these times aerosol loadings were low, with mean number and volume concentrations of 1630 cm −3 and 1.91 μm 3  cm −3, respectively. The aerosol during clean periods was dominated by organics, and exhibited low hygroscopicities (mean κ  = 0.18 at s  = 0.3%). When air was from more populated regions to the east and south (∼29% of the time), aerosol properties reflected a stronger anthropogenic influence, with 85% greater particle number concentrations, 2.5 times greater aerosol volume, six times more sulfate mass, and increased hygroscopicity (mean к  = 0.24 at s  = 0.3%). These trends are have the potential to influence forest–atmosphere interactions and should be targeted for future study. Highlights: Aerosol characterization at PROPHET during the summer 2009 CABINEX study. Air mass origin region had large impacts on nearly all observed aerosol properties. Anthropogenically-impacted air had 85% more particles and 167% more aerosol volume. Anthropogenically-impacted air also had increased sulfate and greater hygroscopicity.